Management of dental caries lesions in Latin American and Caribbean countries - Amaury POZOS-GUILLÉN; Gustavo MOLINA; Vera SOVIERO; Rodrigo Alex ARTHUR; Daniel CHAVARRIA-BOLAÑOS; Ana María ACEVEDO (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract Caries management at the lesion level is dependent on the lesion activity, the presence of a cavitation (either cleanable or non-cleanable), and lesion depth as evaluated via radiographic examination. A variety of non-invasive, micro-invasive, and minimally invasive treatment (with or without restoration) options are available for primary and permanent teeth. Non-invasive strategies include oral hygiene instructions, dietary counseling, and personal as well as professional use of fluoridated products that reduce demineralization and increase re-mineralization. Micro-invasive procedures include the use of occlusal resin sealants and resin infiltrants, while minimally invasive strategies comprise those related to selective removal of caries tissues and placement of restorations. Deep caries management includes indirect pulp capping, while exposed pulp may be treated using direct pulp capping and partial or complete pulpotomy. The aim of the present study was to review available evidence on recommended preventive and restorative strategies for caries lesions in Latin American/Caribbean countries, and subsequently develop evidence-based recommendations for treatment options that take into consideration material availability, emphasize ways to adapt available treatments to the local context, and suggest ways in which dentists and health systems can adopt these treatments.